PENENTUAN LANDAS KONTINEN EKSTENSI BATAS MARITIM INDONESIA-PALAU PADA KEDALAMAN 2500 M ISOBATHS + 100 NM DI SEBELAH UTARA PAPUA MENGGUNAKAN BATIMETRI TURUNAN DATA PENGINDERAAN JAUH - Julzarika, Atriyon; Susanto, Susanto (Badan Informasi Geospasial in Partnership with MAPIN, 2010)
Northern Papua Indonesia is a region that directly adjacent to Palau in Pasific Ocean. This condition allows Indonesia to claim maritime boundary delimitation according to Technical Aspect of the Law of the Sea (TALOS), one of TALOS concept is to determine extended continental shelf in -2500 m depth isobaths + 100 nm in 1% sedimentary rock. This extended continental shelf can be determined by using bathymetry that is derived from altimetry satellite imagery. The establishment of this bathymetry has the same concept with topography in the case of survey mapping and remote sensing. Those bathymetry can be applied to determine another maritime boundary delimitation claims. Besides that, those bathymetry can also be applied to make a 3D model of bathymetry in Pasific Ocean so we can observe the condition of internal waters, medium and depth waters in the northern Papua Indonesia. This bathymetry will be useful for various engineering applications and some other of non engineering applications. This 3D model of bathymetry will be useful for Indonesia in claiming maritime boundary delimitation in Pasific Ocean and to improve marine resources management.Keywords : Bathymetry, Northern Papua, extended continental shelfABSTRAKWilayah Papua utara Indonesia merupakan kawasan yang berbatasan langsung dengan Palau di Samudera Pasifik. Kondisi ini memungkinkan Indonesia dapat mengklaim batas maritim sesuai dengan yang terdapat di Technical Aspect of the Law of the Sea (TALOS). Salah satunya adalah penentuan batas landas kontinen ekstensi pada kedalaman -2500 m isobaths + 100 nm pada sedimentasi 1%. Batas landas kontinen ini dapat ditentukan menggunakan data batimetri yang diturunkan dari citra satelit Altimetri. Pembuatan batimetri ini memiliki konsep yang sama dengan pembuatan topografi secara survei pemetaan maupun secara penginderaan jauh. Batimetri tersebut bisa digunakan untuk penentuan klaim batas maritim lainnya. Selain itu, batimetri tersebut bisa juga digunakan untuk pemodelan 3D perairan di Samudera Pasifik sehingga akan terlihat kondisi perairan dangkal, sedang, dan dalam yang ada di sebelah utara Papua. Batimetri ini akan berguna dalam berbagai aplikasi keteknikan dan non keteknikan lainnya. Pemodelan 3D perairan ini akan berguna bagi Indonesia dalam klaim batas maritim di Samudera Pasifik dan dalam pengelolaan sumber daya alam laut.Kata kunci: Batimetri, Papua Utara, landas kontinen ekstensi